2016
DOI: 10.1007/s10753-016-0440-1
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Gas Inhalation Attenuates Seawater Instillation-Induced Acute Lung Injury via the Nrf2 Pathway in Rabbits

Abstract: Seawater instillation-induced acute lung injury involves oxidative stress and apoptosis. Although hydrogen gas inhalation is reportedly protective in multiple types of lung injury, the effect of hydrogen gas inhalation on seawater instillation-induced acute lung injury remains unknown. This study investigated the effect of hydrogen gas on seawater instillation-induced acute lung injury and explored the mechanisms involved. Rabbits were randomly assigned to control, hydrogen (2 % hydrogen gas inhalation), seawa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 27 publications
2
20
0
Order By: Relevance
“…How HRS activates the HIF-1 α pathway to induce autophagy remains unclear. There are two ways of enhancing the activity of HIF-1 α , either to enhance the synthesis of HIF-1 α , such as gene transfer or to inhibit the degradation of HIF-1 α [ 51 ]. Subsequent studies have indicated that the anti-inflammatory effect of hydrogen may activate Nrf2 [ 51 ] and its downstream target, heme oxygenase-1 (HO-1), in different experimental models [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…How HRS activates the HIF-1 α pathway to induce autophagy remains unclear. There are two ways of enhancing the activity of HIF-1 α , either to enhance the synthesis of HIF-1 α , such as gene transfer or to inhibit the degradation of HIF-1 α [ 51 ]. Subsequent studies have indicated that the anti-inflammatory effect of hydrogen may activate Nrf2 [ 51 ] and its downstream target, heme oxygenase-1 (HO-1), in different experimental models [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are two ways of enhancing the activity of HIF-1 α , either to enhance the synthesis of HIF-1 α , such as gene transfer or to inhibit the degradation of HIF-1 α [ 51 ]. Subsequent studies have indicated that the anti-inflammatory effect of hydrogen may activate Nrf2 [ 51 ] and its downstream target, heme oxygenase-1 (HO-1), in different experimental models [ 52 ]. Previous studies have indicated that HO-1 can trigger and regulate HIF-1 α expression in hypoxic tumor cells [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since the first report in 2007, (5) accumulating evidence has demonstrated its therapeutic potential against IRI and the underlying mechanisms therein. Currently, H 2 i s known to have 3 definitive effects: antioxidant, (5)(6)(7)(8)(9)(10)(11)(12)(13) anti-inflammatory, (10,(14)(15)(16) and antiapoptosis. (8,17) Though some experimental animal studies have shown its therapeutic potential in organ preservation, eg, lung, (11) heart, (18) kidney, (6) intestine, (7) and liver, (19,20) its clinical use is yet to be applied because of its unfavorable features.…”
mentioning
confidence: 99%
“…Treatment with AL decreased MPO activity in lung tissue. Cellular lipid peroxidation results in MDA generation, which causes cross‐linking and polymerization of proteins and nucleic acids, exerting cytotoxic effects . In this study, AL treatment decreased the MDA content.…”
Section: Discussionmentioning
confidence: 50%